Simultaneous determination of methocarbamol and aspirin by RP‐HPLC using fluorescence detection with time programming: its application to pharmaceutical dosage form. (20th June 2012) - El‐Din, M Sharaf; Eid, M; Zeid, AM
ABSTRACT: A new simple, rapid and sensitive reversed‐phase liquid chromatographic method was developed and validated for the simultaneous determination of methocarbamol (MET) and aspirin (ASP) in their combined dosage form. The separation of these compounds was achieved within 6.0 min on a CLC Shim‐pack C8 column (250 × 4.6 mm, 5 µm particle size) using isocratic mobile phase consisting of acetonitrile and 0.02 M dihydrogenphosphate buffer (30:70, v/v) at pH = 5.0. The analysis was performed at a flow rate of 1.0 mL/min with fluorescence detection at 277/313 nm for MET and 298/410 nm for ASP using real‐time programming. The selectivity, linearity of calibration, accuracy, inter‐ and intra‐day precision and recovery were examined as parts of the method validation. The concentration–response relationship was linear over concentration ranges of 0.02‐0.20 and 0.02‐0.40 µg/mL for MET and ASP, respectively, with a limit of detection of 6 and 32 ng/mL for MET and ASP, respectively. The proposed method was successfully applied for the analysis of both MET and ASP in prepared tablets with average recoveries of 99.88 ± 0.65% for MET and 100.44 ± 0.78% for ASP. The results were favourably compared to those obtained by a reference method. Copyright © 2012 John Wiley & Sons, Ltd.